Inappropriate shock delivery as a result of electromagnetic interference originating from the faulty electrical installation. Issue 5 (25th April 2022) - Babic, Milos D; Tomovic, Milosav; Milosevic, Maja; Djurdjevic, Branko; Zugic, Vasko; Nikolic, Aleksandra
Abstract: We present a case report of a 74‐year‐old male patient with an implantable cardioverter defibrillator who suffered an inappropriate defibrillation shock while bathing in the tub. Insight in the ICD stored electrogram episodes revealed electromagnetic interferences, with a typical 50 Hz electrical artifact mimicking fast ventricular tachycardia as a device misinterpreted. After this event, the maintenance workers investigated the electrical installation in the bathroom and revealed that there was voltage leaking between electrical installation and metal pipes. After the repair was completed without any additional programming, the patient has had no subsequent shocks. Abstract : Inappropriate VF detection and the delivery of the Inappropriate shock as a result of electromagnetic interference originating from the faulty electrical installation.